Methicillin resistance and enterotoxigenicity of Staphylococci isolated from milk and white cheese in Iraq - Al-Khafaji, Marwa; Flayyih, May; Sabah, Majeed (Iraqi Journal of Science, 2023)
Two hundred staphylococcal isolates isolated from milk and white cheese samples, which were collected from local markets in Baghdad. The predominant species was Staphylococcus aureus 97 isolates (48.5%), followed by S.chromogenes 82 (41%) and 21 (10.5%) S.epidermidis isolates. The pattern of antibiotic susceptibility of Coagulase Positive Staphylococci (COPS) and Coagulase Negative Staphylococci (CONS) isolates to 3 antibiotics (Methicillin, Tetracyclin and Vancomycin) was determined using disc diffusion method; the results revealed that 80 S. aureus isolates (82.47%) found to be methicillin resistant (MRSA) while 8 isolates (8.24%) were vancomycin resistant (VRSA) and 18 S. aureus isolates (18.5%) resist tetracycline antibiotic. Sixty four CONS isolates (62.13%) were methicillin resistant, 28 CONS isolates (27.18%) resist tetracycline, and 5 CONS isolates (4.85%) were vancomycin resistant. Suckling mouse bioassay was tested to investigate the staphylococcal enterotoxin biological activity. Results showed that 131 isolates which constitutes 65.5% of the examined isolates, gave a positive result. Both COPS and CONS isolates were shown to be enterotoxigenic, COPS represented by S. aureus species occupied the higher ratio of the enterotoxigenic staphylococci, 86 S.aureus isolates (65.64% of the enterotoxigenic staphylococci) gave the positive ratio of the intestine weight to the body weight which was ≥ 0.083 while 45 CONS isolates (34.35%) were enterotoxin producers. These toxins were thermostable staphylococcal enterotoxins which gave the same toxic effect after heating to 100°C for 30 minutes.